Public management in an information age towards strategic public information management - Meijer, Albert; Ingrams, Alex; Zouridis, Stavros (Bloomsbury Academic, 2023)
This accessible new text, aimed specifically at those studying and working in public management, offers readers a solid understanding of ICTs and their implications for public management. It offers aspiring and current public managers a framework for the development of strategic public information management across the full range of public organizations"--